Working Capital Management and Profitability of Manufacturing Public Company in Indonesia - rahma ayu agustiyana (Faculty of Economics and Business | Universitas Diponegoro, 2020)
Abstract. This research studied the causative link between working capital management (WCM) and return on assets (ROA) in consumer goods companies listed on The Indonesian Stock Exchange. Days Sales of Inventory (DSI), Days Sales Outstanding (DSO), Days Payable Outstanding (DPO) and Cash Conversion Cycle (CCC) were used as WCM metrics. The study was based on micro-data for 39 consumer goods companies with period from 2015 – 2019. By using multiple regression and correlations analysis, the study shows that extending DSO and DPO had a profitable impact on ROA and extending the DSI and CCC had an adverse impact on ROA in consumer goods companies. Keywords : consumer goods industry, profitability, working capital management